2010
DOI: 10.1007/s10755-010-9155-7
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Partnerships: A New Agenda for Higher Education

Abstract: In this article we develop the concept of transformational partnership and illustrate how such an understanding has enriched the relationship between a particular university and a school system. Transformational partnerships are different in purpose, nature, and strategies from transactional partnerships. They are based upon genuine engagement and a focus on common goals and mutual benefits. In transactional partnerships each institution pursues its own goals with little consideration of mutual goals or shared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 10 publications
1
47
0
Order By: Relevance
“…Examples of integrating structures include formation of a center, creation of a central collaboration unit, and supporting technology systems (Kezar, 2005). Similarly, Butcher et al (2011) identified resources as "the financial and human assets that partners contribute to a given project to ensure its success" (p. 38).…”
Section: Key Factors Enabling Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of integrating structures include formation of a center, creation of a central collaboration unit, and supporting technology systems (Kezar, 2005). Similarly, Butcher et al (2011) identified resources as "the financial and human assets that partners contribute to a given project to ensure its success" (p. 38).…”
Section: Key Factors Enabling Collaborationmentioning
confidence: 99%
“…However, networks and relationships cannot go unmanaged, as Duffield et al (2013) spoke of the importance of building "trust" among collaborative partners, and the amount of time necessary to do so. Butcher et al (2011) encouraged collaborative partners to "relate on a basis of trust" (p. 36), and also identified collaborative leadership as an important principle:…”
Section: Key Factors Enabling Collaborationmentioning
confidence: 99%
“…Through our collective work within CFICE, we have identified that CCE can entail a wide range of motivations, objectives and goals. In particular, many CCE partnerships are not based in social and environmental justice frameworks and do not challenge systems of inequality or endeavour to change social and ecological systems (McBride et al 2006;Butin 2010;Butcher et al 2011). While we acknowledge that these types of CCE can still have value for research, teaching and the work of non-profit organizations, we also recognize that these types of CCE can reinforce the status quo and may risk reproducing social inequities and environmental challenges (Dempsey 2010;Mitchell et al 2012).…”
Section: Community Campus Engagement and Social And Environmental Jusmentioning
confidence: 99%
“…So although educational partnerships are almost universally viewed as positive and progressive, care should be taken in making such an assumption. Butcher et al's (2011) analysis of university partnerships with schools and community groups, 'commitment to longterm collaboration in goal setting and to sharing of perspectives, capacities, and resources' was found to be integral to partnerships designed to make a difference. In this study, other forms of partnership that were more transactional in character were found to be necessary for operational reasons, but lacked the capacity to be generative or transformational.…”
Section: Perspectives and Commentary On The Theoretical Literaturementioning
confidence: 99%